Benchmarking jako nowoczesne narzędzie promocji miast i regionów - Śnihur, Janusz (Benchmarking as modern instrument of promotion of city and regions, 2005)
Cities (region), should lead marketing activity in foothold about objective data competing between them, which (who) allow to define site in accordance with other cities „market" city, among others, investment attractiveness in respect, tourist, communication etc. translation of benchmarking is one of such manner of getting data and executing of comparative analysis in accordance with other cities of competitors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 359-368